ANALISIS PENGGUNAAN DDC PADA SISTEM HVAC UNTUK MENINGKATKAN PENGHEMATAN KONSUMSI ENERGI DI HOTEL LANGHAM DISTRICT 8 SCBD JAKARTA - Hadi Chandra, Wibisana; Swamardika, I.B Alit; Maharta Pemayun, A.A Gede (Jurnal SPEKTRUM; Vol 7 No 3 (2020): Jurnal SPEKTRUM, 2020)
Heating System, Ventilanting and Air Conditioning (HVAC) or air conditioning systems become one of the needs in high rise buildings in order to increase comfort in the room, differences in the level of comfort of each individual makes the HVAC system changes in load patterns that can result in wasteful use of electrical energy. This study aims to determine the savings in the use of electrical energy with the use of DDC in the HVAC system at the Langham hotel. DDC can regulate HVAC system supporting devices such as cooling towers, condenser water pumps, chilled water pumps and chillers that aim to reduce the performance of the chillers so that energy savings are obtained. By using 2 work operation methods, the results of the calculation of energy use obtained at the side of the chiller Langham hotel, with manual operation without the use of DDC obtained a total consumption cost of IDR 3,409,290 and automatic work operations using DDC obtained a total consumption cost of IDR 2,601,990 so that it is obtained saving percentage of 24%.